2007
DOI: 10.1093/jn/137.7.1808
|View full text |Cite
|
Sign up to set email alerts
|

Low Intake of Vitamin B-6 Is Associated with Increased Risk of Colorectal Cancer in Japanese Men

Abstract: We investigated the association of dietary intakes of folate, vitamin B-6, vitamin B-12, and methionine with the risk of colorectal cancer in a large prospective cohort study of middle-aged Japanese men and women. A total of 81,184 subjects (38,107 men and 43,077 women) who participated in the Japan Public Health Center-based Prospective Study were followed from 1995-1998 to the end of 2002, during which 526 cases of colorectal cancer (335 men, 191 women) were newly identified. Dietary intake of nutrients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
8
41
1
Order By: Relevance
“…Nonetheless, dietary intake of vitamin B 6 was shown to be related to a decreased risk of colorectal cancer in different populations worldwide, although the findings are not necessarily consistent (Theodoratou et al, 2008;Larsson et al, 2010;Zhang et al, 2012;Zschäbitz et al, 2013). The findings on methionine, vitamin B 2 and vitamin B 12 are in agreement with the observation in the majority of the previous studies (Harnack et al, 2002;Le Marchand et al, 2002;Ishihara et al, 2007;Murtaugh et al, 2007;Sharp et al, 2008;Weinstein et al, 2008;Shrubsole et al, 2009). …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Nonetheless, dietary intake of vitamin B 6 was shown to be related to a decreased risk of colorectal cancer in different populations worldwide, although the findings are not necessarily consistent (Theodoratou et al, 2008;Larsson et al, 2010;Zhang et al, 2012;Zschäbitz et al, 2013). The findings on methionine, vitamin B 2 and vitamin B 12 are in agreement with the observation in the majority of the previous studies (Harnack et al, 2002;Le Marchand et al, 2002;Ishihara et al, 2007;Murtaugh et al, 2007;Sharp et al, 2008;Weinstein et al, 2008;Shrubsole et al, 2009). …”
Section: Discussionsupporting
confidence: 75%
“…While low methionine intake, especially in combination with low folate and high alcohol intake, was related to an increased risk of colorectal cancer (Giovannucci et al, 1995;Razzak et al, 2012), methionine intake was unrelated to colorectal cancer in other studies (Harnack et al, 2002;Le Marchand et al, 2002;Ishihara et al, 2007;Murtaugh et al, 2007;Shrubsole et al, 2009). Vitamin B 2 and B 12 have been unrelated to colorectal cancer risk in many studies of different populations (Harnack et al, 2002;Le Marchand et al, 2002;Ishihara et al, 2007;Murtaugh et al, 2007;Sharp et al, 2008;Weinstein et al, 2008;Shrubsole et al, 2009), while recent studies showed a protective association with plasma vitamin B 2 and with dietary vitamin B 2 (Zschäbitz et al, 2013). The two latter studies found no association with plasma or dietary vitamin B 12 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Findings seem to differ somewhat according to ethnic group (Satia-Abouta et al, 2004). In a study conducted among Japanese participants with relatively high folate exposure, this association was weaker than in studies conducted among other ethnic groups (Ishihara et al, 2007). These results are consistent with another Japanese study that showed a null association, possibly because of an insufficient number of folate-deficient participants, in a hospital-based sample using a case-control design (Otani et al, 2005).…”
Section: Introductionsupporting
confidence: 69%
“…Many recent studies conducted in North America (Le Marchand et al, 2005;Wei et al, 2005;Zhang et al, 2006), Europe Brink et al, 2005;Larsson et al, 2005;Norat et al, 2005;Ravasco et al, 2005;de Vogel et al, 2006;Ferrari et al, 2007;Guerreiro et al, 2007;Mas et al, 2007), Japan (Matsuo et al, 2005;Otani et al, 2005;Ishihara et al, 2007) and China (Jiang et al, 2005) evaluated the association between folate intake and the risk of CRC. Findings seem to differ somewhat according to ethnic group (Satia-Abouta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%